PEMBAGIAN AL KINAYAH DAN CONTOHNYA AL KINAYAH DALAM AL-QUR’AN - Muhammad Zaki Rais; Aansyahduhan (Wahdatul Ulum Institute, 2026)
The Al-Quran is the speech of Allah revealed to humanity to be recited, contemplated (tadabbur), understood, and practiced through its divine messages. The Messenger chosen by Him to receive this revelation is Prophet Muhammad SAW, who came from the Arab nation. Therefore, by His will, the Al-Quran was revealed in the language of that nation, namely Arabic. To properly and correctly understand its contents, we are obligated to know the intricacies within the Al-Quran. Auxiliary sciences in interpreting the Al-Quran are highly necessary—even obligatory—to comprehend deeply and apply to its verses, resulting in an understanding that aligns with the context of the times. Within the Quranic auxiliary sciences, particularly Balaghah, the interpretive principle of Kinayah needs to be discussed, given the varied communicative language of the Al-Quran. Sometimes, it uses language that can be understood textually, while at other times, the Al-Quran employs language not easily grasped from text alone, but also requires understanding the verse’s context. Indeed, the Al-Quran often uses sarcasm, which requires grasping through principles and contextual knowledge along with supporting sciences to comprehend it.